HUBUNGAN BURNOUT AKADEMIK DAN SELF-DIRECTED LEARNING READINESS DENGAN MOTIVASI PADA MAHASISWA KEDOKTERAN UMUM UNIVERSITAS JENDERAL SOEDIRMAN - Heidy Angelina Mulyadi; Karina Evandra Nathaniel; Yochananta Wira (Fakultas Kedokteran Universitas Jenderal Soedirman, 2022)
Medical students often experience academic burnout events due to demands for responsibility of taking care of patients life. Academic burnout defined as both physically and psychologically fatigue that results from academic-related job and emotional demands. Burnout may affect ones study motivation. It can cause lower study motivation that at the end will result achievement decrease. On the one side, Self Directed Learning Readiness (SDLR) is needed to make one reach their goal. Academic burnout, motivation, and SDLR play an important role in high academic performance and achievement, but very few research that focuses on these variables especially in the Faculty of Medicine, Jenderal Soedirmas University. This research aims to find out the correlation of academic burnout and Self Directed Learning Readiness with motivation in Medical Students of Jenderal Soedirman University. This research is an observational study. The subject of this study is Medical Students of Jenderal Soedirman University batch 2020. This study used a sample of 112 students taken with total sampling. The method of collecting data this study used is by questionnaire, which includes Maslach Burnout Inventory-Student Survey (MBI-SS), Motivational Questionnaire Motivated Strategies of Learning Questionnaire (MSLQ) and Self Directed Learning Readiness (SDLR) using the SDLR questionnaire. The results are -0.510 for correlation value between burnout and motivation, 0.406 between motivation and SDLR, -0.359 for direct correlation, and -0.207 for indirect correlation between burnout and SDLR. This means that the value of direct influence is greater than indirect influence. Directly, burnout is concluded to affect motivation and have a significant influence on SDLR.